1998
DOI: 10.1101/gad.12.3.343
|View full text |Cite
|
Sign up to set email alerts
|

DSIF, a novel transcription elongation factor that regulates RNA polymerase II processivity, is composed of human Spt4 and Spt5 homologs

Abstract: We report the identification of a transcription elongation factor from HeLa cell nuclear extracts that causes pausing of RNA polymerase II (Pol II) in conjunction with the transcription inhibitor 5,6-dichloro-1-␤-D-ribofuranosylbenzimidazole (DRB). This factor, termed DRB sensitivity-inducing factor (DSIF), is also required for transcription inhibition by H8. DSIF has been purified and is composed of 160-kD (p160) and 14-kD (p14) subunits. Isolation of a cDNA encoding DSIF p160 shows it to be a homolog of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
711
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(741 citation statements)
references
References 76 publications
28
711
0
2
Order By: Relevance
“…These promoter proximately paused polymerases are the major form of polymerase found bound to metazoan chromosomes and are poised for entry into productive elongation (9,17). Two factors, the DRB Sensitivity Inducing Factor, DSIF (18), and NELF (19), have been clearly implicated in generating poised polymerases (20,21) (Figure 2). Published ChIP-Seq data for Pol II, DSIF, and NELF in MES cells (9) were reanalyzed to generate a genome wide average ( Figure 2B).…”
Section: Promoter Proximally Paused Polymerasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These promoter proximately paused polymerases are the major form of polymerase found bound to metazoan chromosomes and are poised for entry into productive elongation (9,17). Two factors, the DRB Sensitivity Inducing Factor, DSIF (18), and NELF (19), have been clearly implicated in generating poised polymerases (20,21) (Figure 2). Published ChIP-Seq data for Pol II, DSIF, and NELF in MES cells (9) were reanalyzed to generate a genome wide average ( Figure 2B).…”
Section: Promoter Proximally Paused Polymerasesmentioning
confidence: 99%
“…A key feature of transcription of virtually any promoter in vitro using a crude nuclear extract is the inhibition of the generation of long transcripts by the ATP analog 5,6-Dichloro-1-β-Dribofuranosylbenzimidazole (DRB) (16,22). P-TEFb (23), NELF (19) and DSIF (18) were purified based on their activities during reconstitution of DRB-sensitive transcription using fractionated nuclear extracts. Individually, the three factors have almost no effect on elongation of pure Pol II, but together NELF and DSIF reduce the elongation rate of Pol II significantly, and P-TEFb can reverse the negative effect of the two factors (20,21).…”
Section: Promoter Proximally Paused Polymerasesmentioning
confidence: 99%
“…Wada et al (1998a) estimated by gel filtration a native size of >300 kDa and suggested that the Spt5-Spt4 complex is a multimer of the 165-kDa Spt5 protein. Deletion analysis delineated a central Spt4-binding domain on human Spt5 from amino acids 176-313 (Yamaguchi et al 1999;Ivanov et al 2000), but the methods employed (GST pull-downs, co-immunoprecipitations) did not reveal the stoichiometry or size of the complex.…”
Section: Resultsmentioning
confidence: 99%
“…The capping enzymes are directed to nascent mRNAs by binding to the phosphorylated carboxyl-terminal domain (CTD) of the largest subunit of RNA polymerase II McCracken et al 1997;Yue et al 1997;Ho and Shuman 1999;Pei et al 2001;Fabrega et al 2003). Capping enzymes also bind to the Pol II elongation factor Spt5 (Wen and Shatkin 1999;Pei and Shuman 2002), which, in conjunction with its binding partner Spt4, elicits an elongation arrest at promoter-proximal sites (Wada et al 1998a). The Spt5/Spt4-induced elongation arrest in metazoans is alleviated by the Cdk9 protein kinase, a subunit of positive transcription elongation factor b (P-TEFb) (Wada et al 1998b).…”
Section: Introductionmentioning
confidence: 99%
“…Negative factors (N-TEF), such as factor 2 , 1998 and DRB-sensitivity inducing factor (DSIF) Wada et al, 1998), cause premature stopping and termination of initiated polymerase resulting in the generation of only short abortive transcript. Positive factors (P-TEF) enable RNA pol II to overcome the promoter proximal pausing and premature termination and to enter productive elongation Price, 1992, 1995).…”
Section: Cyclin T and Its Physiological Functionmentioning
confidence: 99%